Maternal determinants affecting perinatal mortality: a multivariate statistical approach - Agrawal, Manish; Bhatnagar, Kriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India has made considerable progress over the last two decades in the area of maternal and child health, through innovative and comprehensive health packages that covers the spectrum of Reproductive Child Health (RCH). Awareness of the special vulnerability of the cohort of mothers with ‘high risk factor’ has led to the popular recognition of ‘risk approach’, involving the optimal use of existing MCH services, providing essential obstetrical care for all with early detection of complications and emergency services for those who need it, thus reducing the need for intensive care along with reduction in perinantal mortality. The objective was to assess the prevalence of various maternal risk factors in pregnant women in hospital admissions and their correlation with perinatal mortality. Methods: The present study was carried out on 2050 consecutive deliveries from 1st April 2015 to 31st March 2016 at Department of Obstetrics and Gynecology and Department of Pediatrics, Muzaffarnagar Medical College, Muzaffarnagar Uttar Pradesh, India. All the pregnant women were interviewed and examined in detail at the onset of labor regarding various biosocio-economic characteristics, history of past and present medical and obstetrical complications. Results: The PNMR (93.66/1000 birth) observed in present study was still at a higher level and comparable to that in other studies done by various authors in past in this region. A significantly higher PNMR was observed with increase in maternal age and parity (3 times higher PNMR at >35 years and 2 ½ times higher PNMR at parity >5). Similarly, medical illnesses (3 times higher PNMR) and obstetrical complications (1.5 times higher PNMR) during present pregnancy were showing significant effect on perinatal outcome. In a multivariate analysis, residence (rural /urban), place and number of antenatal visits, gestational age and type of delivery remained as most significant maternal risk factors (p<0.005) after multiple logistic regression of other factors viz. maternal age, height, weight, parity, education, socio-economic status and antepartum anemia. Conclusions: It is heartening to observe that highest risk is associated with simple and easily identifiable factors like, unbooked cases, <3 antenatal visits, severe anemia, age >35 years, parity >5, weight <40 kg, height < 140cm , poor dietary calories, medical and obstetrical complications. These can identified from history only by grass root workers like traditional birth attendants and even elderly female family members. These risk determinants, labeled as simple but ‘high’ high risk are associated with poor perinatal outcome. If these factors are timely identified at community level and appropriately referred by grass root workers, it will significantly reduce perinatal mortality and improve neonatal survival.